2004
DOI: 10.1016/j.jasms.2004.04.027
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of the kinetic method applied in the determination of the proton affinity of the nucleic acid molecules

Abstract: The determination of proton affinity (PA) of 2Ј-deoxyadenosine (dA) is used as a case study for the evaluation of possible drawbacks in the determination of the PA of the nucleic acid molecules by the kinetic method. The observed ⌬PA among the different values obtain for dA by applying this procedure in its different extensions was 0.64 Kcal/mol, which is within the uncertainties of any theoretical or experimental approach. It was demonstrated that nucleosides can be generally used as reference compounds to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…The extensive fragmentation of the A 8 strand should be related to nucleobase thermo‐chemical data. Previous work has shown that adenosine nucleotides are less acidic than thymidine64 ones but adenosine is characterised by a higher gas‐phase basicity,70, 71 making adenine a good leaving group. The influence of DNA sequence on the covalent bond fragmentation from duplexes has been reported and explained by the contribution of weak base stacking 27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive fragmentation of the A 8 strand should be related to nucleobase thermo‐chemical data. Previous work has shown that adenosine nucleotides are less acidic than thymidine64 ones but adenosine is characterised by a higher gas‐phase basicity,70, 71 making adenine a good leaving group. The influence of DNA sequence on the covalent bond fragmentation from duplexes has been reported and explained by the contribution of weak base stacking 27.…”
Section: Resultsmentioning
confidence: 99%
“…However, such a hypothesis cannot be assumed here. Nevertheless, the relative values of gas‐phase basicity of nucleobase70, 71 relative to that of the amino acid66 should influence the zwitterionic forms of deprotonated complexes. With the assumption of zwitterionic form, we hypothesise a competition for proton addition and then a competition for ZW location between the basic adenine base and R or K side chain.…”
Section: Resultsmentioning
confidence: 99%
“…To date, mass spectral studies have been focused towards analysis and structural characterization of deoxyribonucleosides [2][3][4][5][6][7][8][9][10]. While thermochemical properties of individual nucleobases have been well studied experimentally in the gas phase, the studies on nucleosides are limited [11][12][13][14][15][16].Xia et al[11] performed extensive calculations on proton affinities (PAs) of nucleosides by the density functional approach. The PA of the four deoxyribonucleosides, i.e., 2=-deoxyadenosine (dA), 2=-deoxyguanosine (dG), 2=-deoxycytidine (dC), and 2=-deoxythymidine (dT) were reported to be in the order of dG Ͼ dC Ͼ dA Ͼ dT, and this order is similar to the PA order of the free bases (G Ͼ C Ͼ A Ͼ T).…”
mentioning
confidence: 99%
“…They concluded the protonation features of deoxyribonucleosides were less changed compared with the corresponding free bases. Donna et al [12] determined the PA of dA and demonstrated the effective use of the kinetic method for the thermochemical measurement of multifunctional molecules like nucleosides and nucleobases. Besides the wide array of proton affinity studies on deoxyribonucleosides [13][14][15][16], there have been no experimental or theoretical reports on the gas-phase acidities (⌬H acid ) of deoxyribonucleosides.…”
mentioning
confidence: 99%
“…The kinetic method developed by Cooks et al 9. has been successfully applied to a wide range of systems for the determination of various thermochemical properties such as gas‐phase basicity and proton affinity,10–15 gas‐phase acidity (GA),2–8 metal ion affinity,16–19 electron affinity,20–22 ionization energy,23, 24 etc. The determination of the GA of an unknown compound by the kinetic method starts with the formation of proton‐bound dimeric anions, [A − H + B − ], where A − and B − (Eqn.…”
Section: The Kinetic Methodsmentioning
confidence: 99%